2017
DOI: 10.2217/fmb-2017-0049
|View full text |Cite
|
Sign up to set email alerts
|

Phages and Immunomodulation

Abstract: In the past years, the microbiome and its role in the pathophysiology of diseases have gained great interest. The progress of our knowledge in this field opens completely novel prospects for treating disorders, including those which are most challenging to medicine today. Of special interest are studies on the interactions of the microbiome with the immune system. Only recently has the presence of bacteriophages in the microbiome been highlighted, and their potential role in maintaining normal immunity has gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 70 publications
(70 reference statements)
4
96
0
2
Order By: Relevance
“…6 The possible mechanisms of immunomodulating and anti-inflammatory activities of phages have recently been discussed in detail. 7 Those observations have been confirmed and extended by other authors. 8,9 Of particular interest are the recent data of van Belleghem et al, 10 who studied the effect of purified phages on immune responses of human peripheral blood mononuclear cells and showed that their prevailing effect is antiinflammatory.…”
Section: Impact Statementsupporting
confidence: 69%
“…6 The possible mechanisms of immunomodulating and anti-inflammatory activities of phages have recently been discussed in detail. 7 Those observations have been confirmed and extended by other authors. 8,9 Of particular interest are the recent data of van Belleghem et al, 10 who studied the effect of purified phages on immune responses of human peripheral blood mononuclear cells and showed that their prevailing effect is antiinflammatory.…”
Section: Impact Statementsupporting
confidence: 69%
“…Accumulating data indicate that phages may modulate the immune response, contributing to maintenance of immune homeostasis in the gastrointestinal tract and possibly at other sites 11, 17, 18, 19. The recent review discusses in detail those immunomodulating activities of phages 11.…”
Section: Phages As Immunomodulatorsmentioning
confidence: 99%
“…The recent review discusses in detail those immunomodulating activities of phages 11. In brief, phages can diminish T cell activation, alloantigen‐induced immunoglobulin production in vitro and extend the skin allograft survival in naive and sensitized mice 13, 14.…”
Section: Phages As Immunomodulatorsmentioning
confidence: 99%
“…Since then, interest in phage therapy in different aquatic species has gained a lot of interest, among others to control columnaris disease, bacterial cold water disease, edwardsiellosis, enteric septicaemia of catfish, vibriosis, furunculosis, Pseudomonas plecoglossicida infection, Pseudomonas aeruginosa infection, streptococcosis, lactococcosis (Choudhury, Tharabenahalli Nagaraju, Gita, Paria, & Parhi, ), A. hydrophila and P. fluorescens infection (Schulz, Robak, Dastych, & Siwicki, ) and others. More and more often, it is mentioned that phages also directly affect immunity, but most of the work concerns mammalian organisms, in particular humans (Van Belleghem, Dąbrowska, Vaneechoutte, Barr, & Bollyky, ; Dąbrowska, ; Górski et al, , ). There is little data confirming impact of phages on fish immune system.…”
Section: Introductionmentioning
confidence: 99%